Congenital and acquired ocular abnormalities in a dog: Clinical description and management (VETERINARIA, 2025)
Congenital ocular malformations, though rare, are clinically significant anomalies in veterinary ophthalmology. The most commonly observed congenital ocular anomalies in cats and dogs include microphthalmia, colobomatous defects, palpebral agenesis, and dermoids, which may occur either independently or in combination. This case report details the clinical evaluation, diagnosis, and surgical management of a dog presenting with two congenital ocular anomalies concurrently with an acquired disorder. A one-year-old male Anatolian Shepherd Dog was referred to the ophthalmology clinic with bilateral conjunctivitis and prolapse of the third eyelid gland. Ophthalmic examination revealed a well-defined dermoid lesion at the lateral canthus of the upper eyelid in the left eye, accompanied by palpebral agenesis located posterior to the dermoid tissue. The dermoid involved the bulbar and palpebral conjunctiva as well as the dorsal corneal surface. Surgical intervention was performed to excise the dermoid tissue and correct both the third eyelid gland prolapse and palpebral agenesis. Additionally, the prolapsed third eyelid gland in the right eye was surgically repositioned. The postoperative period was uneventful, and the patient was monitored for three months without complications. This report highlights the successful simultaneous surgical correction of ocular dermoid, palpebral agenesis, and third eyelid gland prolapse in a single procedure, demonstrating an effective approach for managing complex congenital ocular anomalies in dogs.
Keywords: Eyelid coloboma; ocular dermoid; ocular malformation; third eyelid gland prolapse